A NUMERICAL SIMULATION OF TEXTURAL EVOLUTION DUE TO OSTWALD RIPENING IN METAMORPHIC ROCKS: A CASE FOR SMALL AMOUNT OF VOLUME OF DISPERSED CRYSTALS - Miyazaki K. (My University, 1996)
This paper presents results of a numerical simulation of textural evolution due to Ostwald ripening, using a discrete diffusion equation in three dimensions. For this simulation, a small volume of dispersed crystals was assumed. When a system consists of layers in which the mean grain size is different, mass transport occurs from a layer with smaller mean size (S-layer) to a layer with larger mean size (L-layer). A simulation involving a two-layer system consisting of the S-layer and the L-layer suggests that evolution of the system strongly depends on the initial size distribution in each layer (Sdg0). Mass transport from the S-layer to the L-layer is more likely to occur when the standard deviation of the initial size distribution (Sdg0) is small. As Sdg0 becomes larger, the mass transport becomes slower, and Ostwald ripening occurs within each layer rather than between layers. The size distribution in the S-layer becomes more symmetric and wider than a Lifshitz-Slyozov-Wagner (LSW) distribution due to removal of the solute from the S-layer. On the other hand, the size distribution in the L-layer approaches the LSW distribution.